Implementation of Self and Peer-Correction Techniques towards Grammatical and Mechanical Accuracy in Writing Essay - Matius Tandikombong; Sushy Teko Patanduk; Yusem Ba'ru; Chindy Ista Masado (Universitas Cokroaminoto Palopo, 2022)
The objective of this research were to find out 1). the level of grammatical and mechanic accuracy in the opinion essays by the third semester students. 2). the difference in the level of grammatical and mechanics accuracy between peer-correction and self-correction technique in writing opinion essay by the third semester students of UKI Toraja. This research is a quantitative research. The population of this research is the third semester students of English study program which consists of 3 classes. To select the sample, the writer uses a cluster sampling technique by selecting two classes. The instrument used to collect data is a written test. The results of the research shows that there were differences in the results of the implementation between the peer-correction technique and the peer-correction technique. The average score of students from the implementation of peer-correction is 76.5 and it is classified into the good category while the score of the self-correction implementation is 57.7 and it is classified into poor category. Therefore, it can be concluded that the peer-corection implementation is better than the selft-corection implementation.